Methane Sensitivity of Pulsed Laser Treated SnO2(Ag) Nanocomposite Layers - S. L. Prakopyeu; P. I. Gaiduk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
This paper reports on the gas sensitivity of SnO2(Ag) layers, consequently formed by magnetron sputtering of Sn + Ag target, oxidation of Sn0.65Ag0.35 layers at the temperature of 650 °С within 30 min and modified by laser radiation pulses at energy density of W = 1.5–3.2 J/cm2. Using transmission electron microscopy and transmission electron diffraction it was found, that Sn0.65Ag0.35 and SnO2(Ag) layers are nanocomposite with average grain size of 100–150 nm. Sn0.65Ag0.35 and SnO2(Ag) layers contain grains of the following phase composition: a tetragonal β-Sn with an orthorhombic Ag3Sn (Sn0.65Ag0.35, magnetron sputtering) and a tetragonal SnO2 (cassiterite) with a face-centered cubic Ag structure (SnO2(Ag), thermal oxidation). The sensitivity of SnO2(Ag) layers with respect to 2000–20 000 ppm methane in the air was obtained from sensitivity S measurements at T = 200–360 °C. It is shown that pulsed laser annealing of SnO2(Ag) layers results in up to 12 % increase of sensitivity of SnO2(Ag) layers to methane in comparison with the initial SnO2(Ag) layers.